Influence of different sources of fat on lipid index of muscle and fat tissue of pigs. (September 2019) - Peric, D; Janjic, J; Markovic, R; Sefer, D; Popovic, M; Baltic, M Z; Laudanovic, M
Abstract: Of the total meat production in Serbia, pork makes up more than one half. This meat is often associated with cardiovascular diseases due to its high contents of fat and saturated fatty acids. The aim of this study was to determine the effect of various sources of fat in pig feeds on lipid indices of fat and muscle tissue of pigs from the point of view of consumer health needs. A total of 30 Yorkshire × Landrace crossbred pigs were divided into three experimental groups of 10 individuals and fed a complete finisher mixture for fattening pigs, with standard raw materials and chemical composition but with differing sources of fat. The results obtained show fat sources in pig feed significantly influenced the lipid indices, and the differences were more pronounced in fat than in muscle tissue of pigs.